Extra-Small Gold Nanospheres Decorated With a Thiol Functionalized Biodegradable and Biocompatible Linear Polyamidoamine as Nanovectors of Anticancer Molecules - Bloise, Nora; Massironi, Alessio; Della Pina, Cristina; Alongi, Jenny; Siciliani, Stella; Manfredi, Amedea; Biggiogera, Marco; Rossi, Michele; Ferruti, Paolo; Ranucci, Elisabetta; Visai, Livia (Frontiers in Bioengineering and Biotechnology, 2020)
This work describes a novel and simple approach for the synthesis of extra-small AuNPs for breast cancer therapy. In brief, a biocompatible and biodegradable polyamidoamine (PAA) bearing 20 %, on a molar basis, SH pendants (AGMA1-SH, P) is employed to stabilize AuNPs of different sizes, that is 2.5, 3.5 and 5 nm in Au core (Au@P), and also decorated with Trastuzumab (Au@PT) for cancer cell targeting. AuNPs characterization demonstrates the efficacy of the method, revealing that AuNPs stability and binding with Trastuzumab are strictly influenced by AuNPs particles size, which affects also its interaction with cancer cells. Indeed, increasing AuNP size endowed them with a more stability, positive surface charge while retaining Trastuzumab folding. Correspondingly, biological studies show that Au@PT of 5 nm diameter (5Au@PT) displays the highest efficacy, specificity to-and uptake by HER-2 overexpressing SKBR-3, without eliciting significant effects on the other cell lines. 5Au@PT effectively triggers cell death by P-AKT survival P-ERK proliferation pathways downregulation, Breast cancer-targeting extra small gold nanoparticles BCL-xL decreasing, BAX protein transduction rising, and uptaking by the cells via classical receptormediated endocytosis. Overall, results highlight a potential green method of synthesizing ANPs from biocompatible polymers, and which optimization could offer an important advancement for developing new anticancer conjugated-AuNPs.